The lucky one - Sparks, Nicholas (New York : Grand Central Publishing, 2009)
Coming into the possession of a photograph of a smiling woman he has never met, a man experiences a chain of fortuitous events that cause him to regard the photograph as a lucky charm, a belief that prompts a heartfelt search for the woman in person.
Keywords: Photographs -- Fiction; Love stories